Incidence of Post-cesarean Section Wound Infections in Emergency and Elective Cases at a Tertiary Healthcare Center in Egypt - Ahmed A. Hussein; Muhammad M. Jebril; Muhamed A. Abdelmoaty (Dubai Medical Journal, 2025)
Introduction: Infections at the site of a cesarean section (CS) can lead to longer hospital stays, increased medical costs, and a range of other health complications, including higher mortality rates. For women who experience postoperative wound infections, the recovery process after a cesarean delivery becomes significantly more challenging.